On the Mechanistic Understanding of Photovoltage Loss in Iron Pyrite Solar Cells. Issue 26 (19th May 2020) - Rahman, Mohammad; Boschloo, Gerrit; Hagfeldt, Anders; Edvinsson, Tomas
Abstract: Considering the natural abundance, the optoelectronic properties, and the electricity production cost, iron pyrite (FeS2 ) has a strong appeal as a solar cell material. The maximum conversion efficiency of FeS2 solar cells demonstrated to date, however, is below 3%, which is significantly below the theoretical efficiency limit of 25%. This poor conversion efficiency is mainly the result of the poor photovoltage, which has never exceeded 0.2 V with a device having appreciable photocurrent. Several studies have explored the origin of the low photovoltage in FeS2 solar cells, and have improved understanding of the photovoltage loss mechanisms. Fermi level pinning, surface inversion, ionization of bulk donor states, and photocarrier loss have been suggested as the underlying reasons for the photovoltage loss in FeS2 . Given the past and more recent scientific data, together with contradictory results to some extent, it is timely to discuss these mechanisms to give an updated view of the present status and remaining challenges. Herein, the current understanding of the origin of low photovoltage in FeS2 solar cells is critically reviewed, preceded by a succinct discussion on the electronic structure and optoelectronic properties. Finally, suggestions of a few research directions are also presented. Abstract : Iron pyrite (FeS2 ) is predicted to be the lowest‐cost material for solar electricity production. However, its solar energy conversion efficiency is below 3% because of low photovoltage (<0.2 V). The photovoltage loss mechanisms associated with FeS2 as absorber materials in solar cell applications are discussed, followed by recommendation for future research.